Embodiment Principles of Clearing Justice in Consumer Arbitration - Azwir Agus (Faculty of Law, Hasanuddin University, 2018)
The realization of the principle of justice in proving the settlement of consumer disputes through arbitration in Indonesia is equally important. Undeniable, there is a weakness of the consumer protection law, both substantial norms and formal law. This article is normative legal research that refers to norms and legal principles in the legislation or court decisions. The results show that the proof is one of the trials that plays an important role. In general, the verification system is distinguished based on civil law and common law understandings influenced by various proof system theories such as the presumption of liability principle adopted in the Indonesian consumer protection law. The principle of justice in the consumer arbitration system is different from the arbitration verification system that is universally applicable in Indonesia. The ultimate goal of choosing consumer arbitration is to get substantial justice that is more dignified and not just obtaining formal justice.